2016
DOI: 10.1002/ar.23381
|View full text |Cite
|
Sign up to set email alerts
|

Down‐Regulation of miR‐19a as a Biomarker for Early Detection of Silicosis

Abstract: The accumulated data indicate that there is significant genetic heterogeneity underlying the etiology of silicosis. Recent reports have revealed that microRNAs (miRNAs) play an important role in regulating pulmonary fibrosis. This study, therefore, aimed to identify some miRNAs as biomarkers for silicosis, and to explore the early diagnostic value of biomarkers for silicosis. Total RNAs were collected from the peripheral blood leukocytes of 23 silicosis patients and 23 healthy controls, the different miRNAs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Meanwhile, Yang et al . reported that downregulation of miRNA‐19a acts as an early detection biomarker of SPF . Our results identifying miRNA‐4508 as a diagnostic biomarker of SPF will further enrich the field of SPF biomarker research.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Meanwhile, Yang et al . reported that downregulation of miRNA‐19a acts as an early detection biomarker of SPF . Our results identifying miRNA‐4508 as a diagnostic biomarker of SPF will further enrich the field of SPF biomarker research.…”
Section: Discussionsupporting
confidence: 52%
“…The miRNA expression data of the peripheral blood leucocytes from three SPF cases and controls were downloaded from the Gene Expression Omnibus (GEO) data set (GSE80555) (http://www.ncbi.nlm.nih.gov/geo/), which uses the Human microRNA OneArray v5 (Phalanx Biotech Group, Taiwan, China) as a platform to identify miRNA as SPF biomarkers …”
Section: Methodsmentioning
confidence: 99%
“…The qPCR reaction conditions were 40 cycles of 95°C for 30 s, 95°C for 5 s, and 60°C for 30 s. The PCR results were verified by the melting curve. Relative expression was calculated by the cycle threshold (Ct) values and the 2 -△△Ct method using β-actin as an internal control [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information concerning primer sequences is shown in Supplementary Table 8. Results were quantified using Ct values (delta-delta Ct) method [95].…”
Section: Rna Extraction and Qrt-pcrmentioning
confidence: 99%